Implementasi Terapi Realitas WDEP+AC Terhadap Peningkatan Kontrol Diri Korban Penyalahgunaan Napza di Yayasan Sekar Mawar - Khair, Ummul; Supiadi, Epi; Hakim, Moch. Zaenal (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2024)
WDEP+AC reality therapy is therapy with the Want, Doing, Evaluation, Planning, Acceptance, and Commitment procedures. WDEP+AC reality therapy is a development of Want, Doing, Evaluation Reality Therapy. WDEP+AC Reality Therapy uses a cognitive approach that aims to analyze the effect of WDEP+AC reality therapy on increasing the self-control of drug abuse victims at the Sekar Mawar Foundation. The specific aim of this research is to analyze the level of self-control of drug abuse victims before, during, and after the implementation of WDEP+AC Reality Therapy. The research method used is quantitative research with an experimental model. This research uses a Single Subject Design (SSD) with a Reversal A-B-A design. The target behavior observed in this research is lazy behavior, unable to express oneself, and being easily distracted/unable to determine priorities The instruments used were observation, interviews, questionnaires, and documentation studies. The subjects in this study were three victims of drug abuse at the Sekar Mawar Foundation who were inpatient residents, were no longer drug dependent, were male, and had behavior that lacked self-control. Based on the results of the data analysis that has been carried out, it can be concluded that WDEP+AC Reality Therapy is effective in increasing the self-control of drug abuse victims at the Sekar Mawar Foundation. This is proven by the decrease in the behavior of the three research subjects, namely ES, DK, and BG. WDEP+AC Reality Therapy can be a reference in refining the concept of reality therapy and contributes to providing the development of a reality therapy model in social work practice with drugs.